Ductal Cysts of the Accessory Lacrimal Glands: CT Findings - Khoury, Nabil J.; Haddad, Maurice C.; Tawil, Ayman N.; Ma'luf, Riad N. (American Journal of Neuroradiology, 1999)
Summary: Benign ductal cysts of the accessory lacrimal glands are uncommon lesions of the orbit, arising from the glands of Wolfring and Krause. We report two patients with histopathologically proved cysts in whom CT scans revealed well-circumscribed extraconal cystic lesions adjacent to the globe, involving both eyelids. Radiologists should be aware of these rare lesions so as to include them in the differential diagnosis of orbital cysts.